Early Detection Of Thalassemia Carrier In Patients With SystemicLupus Erythematous: The Use of Shine and Lal Index - Edhyana Sahiratmadja (Indonesian Journal of Rheumatology, 2025)
Background: Anemia in systemic lupus erythematous (SLE) is common due toimpaired erythropoietin response and the presence of antibodies that attackerythropoietin. Various anemia in SLE include autoimmune hemolytic anemia (AIHA),anemia of chronic disease (ACD), or iron deficiency anemia (IDA). Interestingly,Indonesia lies in thalassemia belt area and it is estimated to harboring around 6-10%thalassemia carrier in its population. Therefore, anemia in SLE patients should befurther examined for its possibility for thalassemia carrier. This study aimed todetermine whether a simple erythrocyte index could be used for thalassemia carrierearly detection of SLE patients living in Indonesia. Methods: This study had aretrospective and cross-sectional design, collecting hematology data of SLE patientsregistered at Dr. Hasan Sadikin General Hospital. Erythrocyte indices, includingMentzer index (MCV/RBC) and Shine & Lal index (MCV.MCH.MCH/100), wereassessed to determine IDA or thalassemia carrier. Results: Of 259 hematology datafrom SLE patients included, predominantly female (95.8%), aged 34 years old (median;range 17-65 years) and single (27%), of whom 45.2% had anemia. However, most ofthem were anemia normocytic or normochromic. Interestingly, Mentzer index (<13) wasfound in 2.7% and Shine & Lal index (<1530) in 10% patients, suggesting considerthalassemia carrier. Conclusion: Although Shine & Lal index has lower sensitivitycompared with Mentzer index, Shine & Lal Index might serve a broader screening toolas an early detection for thalassemia carrier.